Nursing in neonatal intensive care: the look of the families - Leticia Gramazio Soares; Vanessa Ferreira de Lima; Larissa Gramazio Soares; Tatiane Baratieri; Maria Luciana Botti (Rev Rene)
Exploratory, qualitative and descriptive study aimed at identifying the perception of the Neonatal Nursing of mothers and / or parents of newborns in intensive care. Data were collected from May to July/2012, with seven couples of parents and two mothers of neonates hospitalized in intensive care, through semi-structured interviews. Data were analyzed from categories. The results showed that parents see the nurse as responsible for the health of humanized night-watch; perceive nursing as a substitute for maternal care; relate negative feelings about the Neonatal Intensive Care Unit and perceive the technical skill as a care factor. Despite the short contact of parents with nursing at the venue of the study, it was possible that parents recognize the figure of the nurse emphasize the humanization of care, but do not realize managerial skills and use of scientific knowledge in nursing practice.